Bacterial etiology in cell phones of health personnel from a clinic in Chiclayo: Etiología bacteriana en teléfonos celulares del personal de salud de una clínica de Chiclayo - De la Cruz-Cueva , Alexander Alexis (2024)
The study aimed to describe the etiology and bacterial frequency on the cell phones of healthcare personnel at the Hospital de Clínicas de Chiclayo, Peru, from March to August 2022. Thirty phones from doctors, nurses, and technicians in hospitalization areas and the Intensive Vigilance Unit (IVU) were analyzed. Samples were taken from the phone screens, cultured, and bacteria were identified using biochemical tests. The data was recorded and analyzed with Microsoft Excel 2013. Bacterial colonization was found on 56.7% of the phones: Gram-positive bacteria on 33.3% and Gram-negative bacteria on 23.3%. Staphylococcus coagulase-negative (35.3%) and Escherichia coli (23.5%) predominated in hospitalization, while Staphylococcus aureus (23.5%) predominated in the IVU. 66.7% of the personnel rarely disinfected their phones, and 40% washed their hands infrequently. Staphylococcus coagulase-negative, S. aureus, and E. coli were the most frequent agents, suggesting deficiencies in hospital hygiene practices.